Macroeconomic determinants of inclusive growth in South Africa: An application of the autoregressive distributed model - Makala, Zizo; Kusairi, Suhal; Makhetha-Kosi, Palesa; Kapingura, Forget Mingiri (Asian Journal of Economic Modelling, 2025)
Despite South Africa’s economy being more advanced than most emerging African economies, it remains the most inequitable country in the world, revealing that regardless of the growth strides, the benefits of growth are barely equitably distributed among the different society groups in the country. Literature indicates that while economic growth is essential, it is insufficient for improving living standards for many South Africans. Against this background, the study examines the factors driving inclusive economic growth in the country using macro data from 1991-2020. A model based on the Social Opportunity Function was estimated to link the measure of inclusive growth and its determinants in the study. The ARDL bounds testing approach to cointegration was employed to evaluate the effect of the different variables employed in the study on inclusive growth. The results show a long-term positive impact of initial income levels, foreign direct investment (FDI), population growth, and trade on inclusive growth, while gross fixed capital formation and inflation negatively affect inclusivity. These findings imply that the government must continue to address the challenges of unequal access to opportunity and skewed income distribution in the country. Moreover, authorities should pursue policies to improve macroeconomic stability to increase FDI inflow and eliminate barriers that prevent it. This will foster inclusiveness in economic growth.